2016
DOI: 10.1002/2016tc004152
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic inversion in the Wandel Sea Basin: A new structural model of Kilen (eastern North Greenland)

Abstract: The seminunatak Kilen in eastern North Greenland, with its complexly deformed Carboniferous‐Cretaceous strata, is a key area to understand the tectonic history of the transform plate boundary between eastern North Greenland and Svalbard. Detailed 3‐D geological mapping from oblique photogrammetry along with limited ground fieldwork and interpretation of previously published data forms the basis for a new structural model of Kilen. Previous structural models interpreted rhombic‐shaped fault patterns as the evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(59 citation statements)
references
References 51 publications
3
56
0
Order By: Relevance
“…Initial mapping and dating of key units resulted in the recognition of 23 lithostratigraphic units of Jurassic-Cretaceous age and an Upper Palaeozoic mélange unit (Pedersen, 1989;Håkansson et al, 1993Håkansson et al, , 1994a. More recent fieldwork by the Geological Survey of Denmark and Greenland (GEUS) (Bojesen-Koefoed et al, 2014) has indicated the need for a stratigraphic revision and a more simplified stratigraphic scheme is applied here to divide the succession into five units cf., Svennevig et al (2016a) (Fig. 3).…”
Section: Geological Settingmentioning
confidence: 99%
See 4 more Smart Citations
“…Initial mapping and dating of key units resulted in the recognition of 23 lithostratigraphic units of Jurassic-Cretaceous age and an Upper Palaeozoic mélange unit (Pedersen, 1989;Håkansson et al, 1993Håkansson et al, , 1994a. More recent fieldwork by the Geological Survey of Denmark and Greenland (GEUS) (Bojesen-Koefoed et al, 2014) has indicated the need for a stratigraphic revision and a more simplified stratigraphic scheme is applied here to divide the succession into five units cf., Svennevig et al (2016a) (Fig. 3).…”
Section: Geological Settingmentioning
confidence: 99%
“…Abbreviations: KCTZ -Kap Cannon Thrust Zone, TLFZ -Trolle Land Fault Zone, TLFS -Trolle Land Fault System, EGFZ -East Greenland Fault Zone, HFFZ -Harder Fjord Fault Zone. difficult ( Fig. 2; Håkansson et al, 1993Håkansson et al, , 1994aSvennevig et al, 2016a). Initial mapping and dating of key units resulted in the recognition of 23 lithostratigraphic units of Jurassic-Cretaceous age and an Upper Palaeozoic mélange unit (Pedersen, 1989;Håkansson et al, 1993Håkansson et al, , 1994a.…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations